Physical education teaching in Italian primary school: theoretical lines and operational proposals - Gaetano Altavilla; Rosario Ceruso; Giovanni Esposito; Gaetano Raiola; Francesca D'Elia (IP Iermakov S.S., 2022)
Background and Study aim.  For the new reform to be applied in the best possible way, it is a priority and useful to promote the development of knowledge on the organization and methods of teaching/learning in physical education in primary school. This study aims to search for a new didactic organizational model for physical education in primary school, starting from the theoretical lines, showing the contrasts of the significant aspects and the uniqueness of heuristic learning, with a consequent theoretical and argumentative elaboration of operational proposals. Material and Methods. For this purpose, an accurate survey of the scientific literature has been analyzed, highlighting the critical issues that characterized the various proposals and attempt to implement physical activity and sports education courses in primary school over the years, up to the recent legislative innovation. Results. The path of the definition of physical education in primary school was marked by stages that did not always enhance the educational and training dimension of the motor and sports experience, making the school discipline assume a marginal and optional role in the face of an extracurricular practice characterized by a widespread organization and more capable of intercepting and responding to the physical exercise and sport needs of society. This complex situation has only generated confusion without solving the problem of the absence of physical and sporting activity in the 5-10 age group, as required by the World Health Organization and the European Union, by adequately and uniquely qualified teachers. It is now useful to promote the development of knowledge on the didactic organization of the primary school, on the different teaching/learning methods in physical education, to contextualize the scope of the new legal provision to the current legal framework Conclusions. The study highlights the value of a new approach in teacher training that aims to ensure the acquisition of key competence, according to the Recommendation of the European Parliament. This perspective can be easily realized by using a core curriculum uniformly applied at the national level.